Estimating the prevalence of intrinsic capacity decline: A systematic review and meta-analysis using WHO's integrated care of older people (ICOPE) screening tool - Vinothini Jayaraj; Sridevi Gnanasekaran; Yazhini VB; Mohanraj Palani Selvam; Navin Rajendran; Gitashree Dutta; Tarun Kumar; Chandrashekar Babu; Vinoth Rajendran (Archives of Gerontology and Geriatrics Plus)
Background: Intrinsic capacity, the combination of physical and mental abilities, is vital for healthy aging. As the elderly population is projected to double by 2050, preserving the well-being of older adults necessitates a comprehensive understanding of and intervention in intrinsic capacity decline. This study aims to assess the pooled prevalence of intrinsic capacity impairment using WHO's ICOPE screening tool. Methods: The systematic review used PRISMA guidelines, conducting an extensive search across multiple databases such as PUBMED, SCOPUS, CINHAL and Google Scholar. The articles that have assessed the intrinsic capacity with various domains like locomotion, cognition, psychology, vitality, vision, and hearing using WHO ICOPE tool were included in this review. We evaluated the risk of bias in cross-sectional studies using the modified Joanna Briggs Institute criteria. Results: A total of nine studies were included for this review, involving participants from various regions all over the world. The pooled prevalence of intrinsic capacity impairment was 55.0 % in the Random Effects Model. While assessing for various domains, the pooled prevalence of locomotion, cognition, psychology, vitality, vision, and hearing was found to be 17.5 %, 18.2 %, 12.1 %, 8.5 %, 17.9 % and 14.4 % respectively. Conclusion: This meta-analysis contributes a comprehensive overview of intrinsic capacity decline prevalence, offering valuable evidence for policymakers and healthcare stakeholders. The findings underscore the urgency of implementing targeted interventions to promote healthy aging and intrinsic capacity preservation worldwide.